2005
DOI: 10.1538/expanim.54.309
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitric Oxide Synthase Inhibitor on the Digestive System Measured by Simultaneous Monitoring of Gastric Motility, Gastric Emptying Activity and Postprandial Pancreaticobiliary Secretion in Dogs

Abstract: Relationships between the NO synthase inhibitor and gastric and pancreaticobiliary functions measured simultaneously in the digestive

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Whether CCK actually induces the drop in fundic tone in a NO-dependent fashion has yet to be elucidated ( Kindt and Tack, 2006 ). In dogs, gastric contractility and emptying are suppressed after treatment with a competitive NOS inhibitor ( Tanaka et al, 2005 ). CCK induces contractions of the smooth muscle of the colon by interacting with the CCK1R in humans ( Morton et al, 2002 ).…”
Section: Cholecystokininmentioning
confidence: 99%
“…Whether CCK actually induces the drop in fundic tone in a NO-dependent fashion has yet to be elucidated ( Kindt and Tack, 2006 ). In dogs, gastric contractility and emptying are suppressed after treatment with a competitive NOS inhibitor ( Tanaka et al, 2005 ). CCK induces contractions of the smooth muscle of the colon by interacting with the CCK1R in humans ( Morton et al, 2002 ).…”
Section: Cholecystokininmentioning
confidence: 99%
“…Previous studies have shown that NO synthase inhibitors delay gastric emptying of solids or liquids in rats (23) and dogs (24)(25)(26). The increase in endogenous NO after smoking cessation may cause relaxation of the pylorus and accelerate gastric emptying.…”
Section: Discussionmentioning
confidence: 98%
“…Conversely, reduction of the nitrergic storage capacity in the fundus is thus expected to accelerate liquid emptying as was observed in the male sGCα 1 KO mice 15 min after gavage. However, most studies investigating the influence of NOS inhibitors on gastric emptying report that NOS inhibition delays gastric liquid emptying (Plourde et al 1994; Tanaka et al 2005), which can be ascribed to increased pyloric tone by inhibition of nitrergic relaxation in the pylorus; this will counteract the stimulating effect on liquid emptying of decreased gastric accommodation capacity (Anvari et al 1998). Also NOS‐1 and cGKI KO mice show delayed gastric liquid emptying (Pfeifer et al 1998; Mashimo et al 2000) corresponding with pyloric hypertrophy (Huang et al 1993) leading to gastric dilatation (Huang et al 1993; Ny et al 2000).…”
Section: Discussionmentioning
confidence: 99%